The first ten years of the Slimbridge collection - Scott, Peter (Wildfowl, 1957)
A complete collection of the Anatidae would consist of at least one pair of each of the 247 different kinds known to science. No such collection of living birds has ever been assembled, or probably ever will be. Nevertheless, most ambitious collectors hope to make their collections as complete as possible. At present the collection at Slimbridge consists of some 1300 birds of 147 different forms. It is the most representative collection in the world, and probably the most representative that there has ever been.